Estudo de fenótipos celulares em pacientes com lúpus eritematoso sistêmico, sob tratamento - Cristina de Mello Gomide Loures (2014)
Systemic lupus erythematosus (SLE) is a multisystemic autoimmune disorder with an etiology that is not yet well understood. Its a rare disease, with the incidence of 8.7 per 100.000 inhabitants of Brazilian population and often occurring in young women during their childbearing years. The immune dysfunction caused by SLE leads to a large production of autoantibodies and immune complexes, excessive complement activation, and an insidious tissue inflammation. Among the diverse clinical manifestations of SLE, lupus nephritis (LN) is the most relevant in SLE, occurring in 50% of patients at diagnosis and in 60% of patients during the course of the disease. The pathogenesis of the disease is extremely complex, with several studies showing alterations of lymphocyte phenotypes. The aim of this study was to determine the imune system alterations in patients with SLE under treatment and compare such alterations in the active and inactive forms between themselves, and with the controls. We have studied a total of 30 patients with SLE under treatment and, as controls, 11 subjects without the disease. NK, T and B cells markers such as CD3, CD4, CD8, CD16, CD19, CD25, CD56, HLA-DR, NKG2D and FoxP3 were assessed in lymphocytes from peripheral blood through flow cytometric assays. NK t cells showed to be decreased only in patients with the active form of the disease, while the TCD4+, T reg FoxP3+ and B cells populations showed to be decreased in patients with SLE, in both active and inactive forms, as compared to control. Conversely, T CD8+ cells population showed to be increased in patients with SLE, with both active and inactive forms. Also, it was observed an increase in the NKG2D activity in CD3+CD56- cells in patients carrying lupic nephritis (LN) compared to non carriers, while TCD4+ and B cells populations showed to be decreased in patients with LN compared to controls. In contrast, T CD8+ cells have been increased in SLE patients with and without LN. Concerning to the main medicines used by patients with SLE, azathioprine intake did not affect the NK, T and B expression profiles, nor even higher or lower prednisone dose. Conversely, hydroxychloroquine users showed a higher expression of NK cells markers compared to non users. In spite of the users to be under treatment, the data taken together allow to confirm the characteristic immune system dysfunction of the SLE, as well variations in the cellular phenotypic profile according to the disease status.